Competing and co–existing business models for EV: lessons from international case studies. (10th April 2015) - Weiller, Claire; Shang, Tianjiao; Neely, Andy; Shi, Yongjiang
This paper presents four innovative business models that are being developed in three countries to support the commercialisation of electric vehicles (EVs). Using an original business model framework and interviews with EV company founders and directors, we analyse the coexistence of competing business models (China) and partnership strategies along the EV value chain (USA and France). Findings emphasise the importance of designing flexible business models and leveraging resources and inter–industry partnerships in the emerging EV ecosystem. The results provide practical recommendations for industrial players and insights for policy–makers.